2019
DOI: 10.1002/ejic.201801221
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) and (I) Complexes of Diphosphine‐Ketone Ligands: Catalytic Activity in Hydrosilylation Reactions

Abstract: The hydrosilylation of unsaturated compounds homogeneously catalyzed by cobalt complexes has gained considerable attention in the last years, aiming at substituting precious metal‐based catalysts. In this study, the catalytic activity of well‐characterized CoII and CoI complexes of the pToldpbp ligand is demonstrated in the hydrosilylation of 1‐octene with phenylsilane. The CoI complex is the better precatalyst for the mentioned reaction under mild conditions, at 1 mol‐% catalyst, 1 h, room temperature, and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The experiments conducted are in favor of a classical mechanism involving a cobalt‐hydride as the active catalyst. In our case as for others [26c,27a,f,i,j] the hydrosilylation catalytic reaction works without any hydride additive, therefore the formation of the active Co−H species may result from σ‐bonds interchange at the metal center by the so‐called sigma‐bond metathesis [34] . Coordination of the ketone and its insertion into the Co−H bond leads to an alkoxo complex which upon reaction with the silane regenerates the active Co−H complex and releases the silyl ether (Scheme 5).…”
Section: Resultsmentioning
confidence: 95%
“…The experiments conducted are in favor of a classical mechanism involving a cobalt‐hydride as the active catalyst. In our case as for others [26c,27a,f,i,j] the hydrosilylation catalytic reaction works without any hydride additive, therefore the formation of the active Co−H species may result from σ‐bonds interchange at the metal center by the so‐called sigma‐bond metathesis [34] . Coordination of the ketone and its insertion into the Co−H bond leads to an alkoxo complex which upon reaction with the silane regenerates the active Co−H complex and releases the silyl ether (Scheme 5).…”
Section: Resultsmentioning
confidence: 95%
“…Reduction of carbonyl compounds by hydrosilylation is a fundamental process in organic chemistry, however, to date most reported catalysts are based on precious metal such as iridium, [45] ruthenium, [46] platinum, [47] or gold [48] . As an alternative, systems based on Earth‐abundant metals including Cu, [49] Ni, [50] and Fe [51] have recently been explored in carbonyl hydrosilylation and showed promising results. Remarkably, processes based on well‐defined cobalt systems for selective hydrosilylation remain quite scarce [52,53] …”
Section: Resultsmentioning
confidence: 99%
“…In the frame of our studies of phosphine-tethered CO and CN π-ligands, we recently reported the Ni(0) coordination of a series of ligands consisting of an imine functionality bridged by two o -phenylene linkers with phosphine substituents (PCNP) (Scheme ). The less bulky ligands afforded tetrahedral Ni(0) complexes Ni­(P Ph CNP Ph )­PPh 3 ( 2 ) and Ni­(P Ph CNP o Tol )­PPh 3 ( 3 ) with the PCNP ligand bound via both phosphine arms and an η 2 ( C , N )-coordination of the imine moiety.…”
Section: Resultsmentioning
confidence: 99%